Indonesia’s Import Licensing Regime after WTO DS 484: Non-Tarif Barriers, Food Security, and Agricultural Trade Law - Bahir Mukhammad (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Indonesia’s food security framework is closely linked to its agricultural trade policies, particularly import licensing mechanisms that often function as non-tariff trade barriers to protect domestic industries. However, tensions arise when such policies conflict with international trade obligations under the World Trade Organization (WTO), as demonstrated in the dispute between Indonesia and Brazil in WTO case DS 484. This study aims to analyze the implications of the WTO DS 484 ruling on Indonesia’s import licensing regime, particularly in relation to non-tariff barriers, food security, and agricultural trade law. The research employed a normative juridical method with a descriptive-analytical approach, supported by literature review and complementary interviews with key stakeholders in the poultry sector. The findings indicate that Indonesia’s import licensing policies have undergone significant revisions to comply with WTO requirements, including the simplification of procedures and removal of certain restrictive measures. Nevertheless, these changes raise concerns regarding increased import competition, which may negatively affect the competitiveness of domestic poultry farmers. Furthermore, although import licensing remains a legitimate regulatory instrument, its application must balance compliance with international trade rules and the protection of national food security. The study concludes that Indonesia needs to strengthen domestic production capacity and pursue food sovereignty strategies to ensure long-term competitiveness while maintaining adherence to WTO obligations. These findings highlight the importance of harmonizing national trade policies with global trade frameworks without undermining the sustainability of domestic agricultural sectors.